2014
DOI: 10.1039/c4mt00047a
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic siderophore production by oil-associating microbes

Abstract: Amphibactin siderophores have been isolated from oil-associated Vibrio spp. following the Deepwater Horizon oil spill, and from Alcanivorax borkumensis SK2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Although genes encoding siderophore uptake proteins are common in HNLC metagenomes, genes encoding siderophore biosynthesis have yet to be reported . A pair of nonribosomal peptide synthetases (NRPS), ABO_2093 and ABO_2092, were recently implicated in the production of amphibactins by the Gammaproteobacteria Alcanivorax borkumensis [Kem et al, 2014]. We identified similar NRPS genes in the genomes of numerous marine Vibrio, and confirmed amphibactin production by five additional NRPS sequence pairs through laboratory culture experiments (supplementary information).…”
Section: Main Textsupporting
confidence: 50%
“…Although genes encoding siderophore uptake proteins are common in HNLC metagenomes, genes encoding siderophore biosynthesis have yet to be reported . A pair of nonribosomal peptide synthetases (NRPS), ABO_2093 and ABO_2092, were recently implicated in the production of amphibactins by the Gammaproteobacteria Alcanivorax borkumensis [Kem et al, 2014]. We identified similar NRPS genes in the genomes of numerous marine Vibrio, and confirmed amphibactin production by five additional NRPS sequence pairs through laboratory culture experiments (supplementary information).…”
Section: Main Textsupporting
confidence: 50%
“…Advanced organic mass spectrometry (ESI-MS) techniques (McCormack et al, 2003) have shown that desferrioxamines, a family of trihydroxamate siderophores, occur at low-pM concentrations in surface waters throughout much of the Atlantic Ocean (Mawji et al, 2008). However, most marine siderophores are structurally very different from terrestrial analogs, even if they contain the same functional groups (Vraspir and Butler, 2009), driving a search for novel amphiphilic ligands, several of which have now been isolated from Fe-limited cultures (Martinez et al, 2000;Kem et al, 2014), or biosynthesized through genomics . More sophisticated procedures are being developed for detecting organic ligands in seawater, either linking conventional ESI-MS with metal-specific extractions, such as immobilized metal affinity chromatography (Ross et al, 2003) and HPLC-ICP-MS (Boiteau et al, 2013), or relying on the power of ultrahigh-resolution FT-ICR-MS (Waska et al, 2015) for a less targeted approach.…”
Section: Introductionmentioning
confidence: 99%
“…They are iron (III) chelators that bacteria secrete to scavenge, solubilise and transport iron (III) inside the cell (Borer, Sulzberger, Reichard, & Kraemer, 2005;Neilands, 1984;Rastogi & Sinha, 2009). Amphibactins produced by Alcanivorax borkumensis SK2 are another example of siderophores used by the bacterium to increase biodegradation (Kem, Zane, Springer, Gauglitz, & Butler, 2014).…”
Section: Marine Bacterial Secondary Metabolites: Structure and Functionmentioning
confidence: 99%